Flexible pavements and climate change: impact of climate change on the performance, maintenance, and life-cycle costs of flexible pavements - Qiao, Yaning (2015)
Flexible pavements are environmentally sensitive elements of infrastructure and their performance can be influenced by climate. Climate change poses a challenge to design and management of flexible pavements in the future. Climate change can occur worldwide and thus all flexible pavements can be exposed to the impact. However, an assessment framework is not available to evaluate the impact of climate change on flexible pavements in terms of performance, maintenance decision-making and the subsequent life-cycle costs (LCC). This research has attempted to develop such a framework. Case studies on six flexible pavement sections from the United States were performed to demonstrate the application of the framework.